Impact of global microchip deficit on the market - Urunbayev Safarbek Samatovich; Safarov Solixjon Sobirjon o’g’li; Iskandarova Mohira Rasul qizi (Zien Journals, 2022)
In this article, worldwide shortage of microchips and the role of microchips in our lives will be discussed. We will also try to find out their contribution to automobile industry and their impact on it. We are going get through the impact of microchip shortage the market in terms of economy. Also, some measures of preventing further shortages will be proposed.
Keywords: Transistors; Microchips; deficit; webcams